Struktur Biaya dan Pendapatan Usahaternak Pembibitan Sapi Potong di Desa Palon Kecamatan Jepon Kabupaten Blora - Rifqi Akmal; Tursina Andita Putri; Narni Farmayanti; Tintin Sarianti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The research focuses on the cattle breeding business in Palon Village, Jepon District, and Blora Regency, which is still considered a secondary source of income by the farmers despite the region's reputation as one of the leading beef cattle producers in Central Java. This perception significantly influences the way farmers manage their cattle breeding businesses. The study analyzes beef cattle breeding operations' cost and income structure. A purposive sample of 30 farmers was selected for the research. Descriptive analysis was used to process the data, cost and revenue structure analysis, and return per cost analysis. The research results show that all breeders use green feed. The cost of providing feed is the largest in beef cattle breeding, reaching 51.13%. Beef cattle breeders also still use family resources, so the contribution of non-cash costs to total costs is significant, reaching 81.16%. Income from cash costs is positive, so farmers still consider this business profitable (farmers do not consider the resources owned by farmers). Considering the total costs, the beef cattle breeding business is inefficient. The capital allocation invested in this nursery business has not provided commensurate returns compared to other sectors. Apart from that, this business can also not provide wages to family workers equivalent to wages for a person-day (HOK).